Correlation Study: Self-Concept and Mathematical Disposition on Learning Outcomes of Elementary School Students - Mawardin Mawardin; Adi Apriadi Adiansha; Mulyadin Mulyadin; Anita Nurgufriani (Journal of Insan Mulia Education, 2023)
The purpose of this study was to determine the correlation of self-concept and mathematical disposition to student learning outcomes, with a total of 153 students. This study uses a survey method with correlation techniques. The research subjects were at Fourth Grade Public Elementary School in Langgudu District, Bima Regency. The results showed that (1) there was a positive relationship between self-concept and student learning outcomes with a correlation coefficient of 0.492 and a determination contribution of 24.2%. (2) There is a positive relationship between mathematical disposition and student learning outcomes with a correlation coefficient of 0.405 with a determination contribution of 16.4%. (3) There is a positive relationship between self-concept and mathematical disposition along with student learning outcomes with a correlation coefficient of 0.579 with a determination contribution of 33.5%. Based on the results of this study it can be concluded that student learning outcomes are related to self-concept and mathematical disposition.